A survey of sewer rehabilitation in Malaysia: application of trenchless technologies - Gupta, B.S.; Chandrasekaran, S.; Ibrahim, S. (Elsevier, 2001)
This work presents a review of applicable sewer rehabilitation options using trenchless technology in Malaysia. The typical problems faced in wastewater collection systems are analysed and factors that determine the selection method are outlined. This study also highlights the necessary steps to be taken prior to the rehabilitation work. The trenchless technology reviewed here comprises repair, renovation and replacement options. The cost-effectiveness of different rehabilitation methods was identified to assess the economic viability of various options in the Malaysian context. This study reveals that not all the trenchless technologies available in the market are suitable for use in Malaysia, mainly due to incompatibility of the rehabilitation materials used. Furthermore, as trenchless rehabilitation generally involves higher capital outlay than open-cut methods, the choice of rehabilitation method has to be made on a case-to-case basis.